2013
DOI: 10.1080/08927014.2013.829049
|View full text |Cite
|
Sign up to set email alerts
|

Understanding urinary conditioning film components on ureteral stents: profiling protein components and evaluating their role in bacterial colonization

Abstract: Ureteral stents are fraught with problems. A conditioning film attaches to the stent surface within hours of implantation; however, differences between stent types and their role in promoting encrustation and bacterial adhesion and colonization remain to be elucidated. The present work shows that the most common components do not differ between stent types or patients with the same indwelling stent, and contain components that may drive stent encrustation. Furthermore, unlike what was previously thought, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 11 publications
0
26
0
3
Order By: Relevance
“… 21 The development of biofilm has also been postulated to attract further bacterial adhesion, possibly leading to infection 22 or predisposing patients undergoing subsequent ureteroscopic intervention to infection. 23 However, we and others have shown no statistically significant association between biofilm formation and increased bacterial adhesion in vitro 24 or postoperative infection in patients. 25 These data suggest that the presence of biofilm may not necessarily result in the development of an UTI, particularly in those patients with intact immune systems.…”
Section: Pathogenesismentioning
confidence: 61%
See 1 more Smart Citation
“… 21 The development of biofilm has also been postulated to attract further bacterial adhesion, possibly leading to infection 22 or predisposing patients undergoing subsequent ureteroscopic intervention to infection. 23 However, we and others have shown no statistically significant association between biofilm formation and increased bacterial adhesion in vitro 24 or postoperative infection in patients. 25 These data suggest that the presence of biofilm may not necessarily result in the development of an UTI, particularly in those patients with intact immune systems.…”
Section: Pathogenesismentioning
confidence: 61%
“… 23 Bacteria will adhere to stents in both the presence and absence of conditioning film. 24 The subsequent development of UTIs was shown to be dependent on stent dwell time. 26 However, stent colonization tends to be polymicrobial while UTIs generally result from a single strain of bacteria, implying that stent-associated infection is likely not a straightforward process, potentially resulting from contamination during the insertion.…”
Section: Pathogenesismentioning
confidence: 99%
“…Hundreds of proteins have been identified as adsorbing to urinary devices in patients. The protein set is diverse and includes cytokeratins, albumin, and inflammatory proteins (50). These conditioning factors likely arise from surrounding cells under inflammatory conditions, as the protein content of urine is generally low.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study by Elwood et al . has suggested that the presence of a conditioning film on catheter surfaces do not increase bacterial adhesion and colonization of urinary device surfaces compared to unconditioned controls [ 34 ].…”
Section: Anti-microbial Coatings To Inhibit Bacterial Growth and Amentioning
confidence: 99%